Voltage Stability and Jacobian Determinant in Power Systems: Analysis, Indicators, and Practical Monitoring Tools - Montoya Giraldo, Oscar Danilo; Pulgarín Rivera, Juan Diego; Torres-Pinzón, Carlos Andrés (Ingeniería, 2026)
Voltage stability is a fundamental aspect of power system reliability, which refers to an electrical network’s ability to maintain acceptable voltage levels under normal operating conditions and various types of disturbances